Telecommuting in Malaysian government offices - Ibrahim, Huda; Mat Aji, Zahurin; Othman, Nafishah; Sheik Osman, Wan Rozaini; Abd Razak, Rafidah; Wahid, Juliana (CGPublisher, 2005)
The Government of Malaysia is working hard to bring the country into a developed and industrialized country by the 2020.To support this development, the government agencies collaborating with non-government agencies increasingly involve in numbers of high technology projects, which must be supported by committed and dedicated service-based civil servants, IT and non-IT professionals.Government-based agencies and institutions, however, are having problems to retain their employees for different reasons; family matters, working distance, unattractive salary and environmental aspects.To solve this problem, the Government should give an opportunity for the employees to work away from offices and to work for more than one employer.In this sense, telecommuting shall become a solution for civil servants in service-based industry and among IT professionals. Employees can work at home or at a remote centre through the use and support of high and reliable ICT infrastructure.The success of telecommuting programs especially in Malaysian environment is depending on numbers of criteria and sub-criteria.This study identified the criteria as rules, regulation and policies, infrastructure, finance, selection, training, environment and benefits.